Reaction paths of alane dissociation on the Si(0 0 1) surface. (16th February 2018) - Smith, Richard; Bowler, David R
Abstract: Building on our earlier study, we examine the kinetic barriers to decomposition of alane, AlH3, on the Si(0 0 1) surface, using the nudged elastic band approach within density functional theory. We find that the initial decomposition to AlH with two H atoms on the surface proceeds without a significant barrier. There are several pathways available to lose the final hydrogen, though these present barriers of up to 1 eV. Incorporation is more challenging, with the initial structures less stable in several cases than the starting structures, just as was found for phosphorus. We identify a stable route for Al incorporation following selective surface hydrogen desorption (e.g. by scanning tunneling microscope tip). The overall process parallels PH3, and indicates that atomically precise acceptor doping should be possible.